2005
DOI: 10.1021/np040245f
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activating Effects of New Alkamides from the Roots of Echinacea Species

Abstract: Chemical investigation of the roots of Echinacea angustifolia, E. purpurea, and E. pallida yielded two new alkamides, identified by analysis of spectroscopic data and comparison with reported alkamides. The new compounds were dodeca-2Z,4E,10Z-trien-8-ynoic acid isobutylamide (1) from E. angustifolia and dodeca-2Z,4E-diene-8,10-diynoic acid isobutylamide (2) from E. purpurea and E. pallida. These two components, as well as previously identified alkamides, exerted inhibition on LPS-mediated activation of a murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 6 publications
8
65
1
Order By: Relevance
“…The results presented in this study demonstrate the inhibition of PGE 2 by several Echinacea species, which may be one process contributing to the reported anti-inflammatory capabilities of these herbs (12). All Soxhlet EtOH extracts from the six species screened, when tested at their highest concentration, reduced PGE 2 levels, except E. purpurea.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The results presented in this study demonstrate the inhibition of PGE 2 by several Echinacea species, which may be one process contributing to the reported anti-inflammatory capabilities of these herbs (12). All Soxhlet EtOH extracts from the six species screened, when tested at their highest concentration, reduced PGE 2 levels, except E. purpurea.…”
Section: Discussionsupporting
confidence: 54%
“…A study performed by Chen et al (12) indicated that alkamides had anti-inflammatory activity as measured by inhibition of nitric oxide (NO) production in LPS-stimulated RAW264.7 cells. NO is a pro-inflammatory mediator that was significantly reduced by total alkamide (a mixture consisting of several alkamides) ranging from 1.6 to 30 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent discovery that dodecadiendiynoic amide 1 from E. purpurea and E. pallida inhibited LPS-mediated activation of a murine macrophage line, RAW264.7, suggests that this alkamide may have anti-inflammatory activity [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Several classes of active constituents have been identified in Echinacea species including caffeic acid derivatives, alkylamides, polyacetylenes, and polysaccharides which are responsible for the anti-inflammatory, immunostimulatory, antioxidant and cicatrising activities of this plant [10]. Actually, the therapeutic use of Echinacea extracts is mostly for the prevention and treatment of upper respiratory tract infections and influenza symptoms [11][12][13]. Echinacea preparations are widely used remedies in Complementary and Alternative Medicine [14].…”
Section: Introductionmentioning
confidence: 99%